Evidence for the Occurrence of Substitution Side Products in Grignard Reactions - Hj. Lajis, Nordin; Khan, Mohammad Niyaz; A. Hassan, Hazimah (1993)
In the formation of Grignard reagents from 4-bromoalkoxybenzene and their subsequent coupling reactions with allylic halides, the unusual minor side products, 8 - 14 have been obtained. © 1993.